Effect of systematic nursing on scar appearance following radical thyroidectomy: a retrospective cohort analysis - Yi Zhang; Fang Liu; Ling Wang; Shuguang Chen; Xiequn Xu; Yaqin Zhang; Shuli Guo; Chengshuai Lv; Xiaoyan Shi; Donglei Shi; Zhiyuan Zhang; Weinan Liu; et al. (Scientific Reports)
Abstract Female patients with thyroid cancer have a greater desire for not only curing the disease but also leaving an inconspicuous scar. Systematic nursing has a comprehensive effect on reducing scar formation. However, comprehensive nursing guidance for postoperative scar management are not usually available for patients with thyroid cancer. This study aimed to compare the comprehensive effect of systematic nursing compared to traditional nursing measures on postoperative scar management in patients with thyroid cancer. One hundred patients who underwent radical thyroidectomy between January 2019 and June 2019 were selected and randomly assigned to two groups. Patients in the experimental group (n = 50) received nursing care under systematic nursing guidance, while those in the control group (n = 50) received traditional nursing care. In the 3rd, 6th, and 12th months after surgery, all patients returned to the general surgery department for scar evaluation. Scarring was evaluated using the Vancouver Scar Scale (VSS). Patients’ self-evaluated satisfaction scores for scar appearance and nursing guidance were also collected. Compared with the control group, scars in the experimental group were less inconspicuous. At the 6th and 12th months after surgery, the total VSS score in the experimental group was significantly lower than that in the control group (P < 0.001). By the 12th month after surgery, patients in the experimental group were more satisfied with the final scar appearance (experimental group: 4.69 ± 0.48; control group: 4.06 ± 0.57; P < 0.01) and nursing care (experimental group: 4.88 ± 0.34; control group: 4.50 ± 0.52; P < 0.05). Systematic nursing guidance had positive effects on reducing scar formation and enhancing patient satisfaction.